(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The study investigated socio-economic factors affecting children hawkers in Moba local government area of Ekiti State. The study adopted the descriptive design of the survey type. The sample size in this study was 50 teachers. Three research questions were raised and answered in the study. The instrument used for data collection was a researcher-designed questionnaire titled “Socio-economic factors affecting hawkers in Moba LGA of Ekiti State.” Data collected were analysed using statistical tools that were employed to answer the research questions such as mean and standard deviation. The findings revealed that high cost of living is associated with street hawking among children. It was also showed that large family size is associated with street hawking among children in Moba Local Government of Ekiti State. The result revealed that poverty is associated with street hawking among children.Based on the results of this study, it was recommended that there is need for government continuous enlightenment of parents on the effect involving their children in street hawking and the importance of education. Government to create more job opportunities so that citizens would be employed to enable then cater for family needs. Government should make education free at all levels so that the less privileged children would have the opportunity to be educated. Government should legislate against involving children of school age in hawking and punish parent, guardian and caregiver who go against it. There is a need to protect the child, advocate reduction in family size, poverty and promote parental education/economic empowerment in order to reduce the urge on children to perform economic roles. They should also improve the standard of living of the citizens through provision of bursary allowance to the indigent citizens.